Sexual orientation disparities in substance misuse: the role of childhood abuse and intimate partner violence among patients in care at an urban community health center. - Reisner, Sari L; Falb, Kathryn L; Wagenen, Aimee Van; Grasso, Chris; Bradford, Judith (Substance use & misuse, 2013)
This study examined disparities in lifetime substance misuse by sexual orientation among 2,653 patients engaged in care at an urban community health center in Boston, MA, as well as the potential mediating roles of childhood abuse <age 15 (CA) and intimate partner violence (IPV). Violence indicators were highly associated with substance misuse, as was identifying as a sexual minority compared to heterosexual. CA and IPV experiences partly explained disparities in substance abuse by sexual orientation with differences seen by sex. Clinicians should assess history of CA and IPV among sexual minorities presenting with a history of substance abuse disorders. The study's limitations are noted.
Keywords: Adolescent; Adult; Adult Survivors of Child Abuse; Aged; Community Health Centers; Female; Health Status Disparities; Humans; Male; Middle Aged; Sexual Behavior; Sexual Partners; Spouse Abuse; Substance-Related Disorders; Urban Population